Karakterisasi Sensori Cheese Tea dengan Metode Check All That Apply (CATA), Emotional Sensory Mapping (ESM), dan Ideal Profile Method (IPM) - Dase Hunaefi; Ziyad Muhammad Farhan (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2021)
Cheese tea is a drink made from a combination of tea and cheese foam. This product is very popular today, and some businesses are interested in developing this product. The objective of this research is to identify the sensory profile of cheese tea through new methods in sensory evaluation: IPM, CATA and ESM. The CATA method is used to define the sensory profile and emotional characteristics of the cheese tea product and the IPM method is used to optimize the product by collecting the ideal customer information. The number of panelists used for each test was 30. The selection was based on the frequency of cheese tea consumption 1 to 2 times per week. Attributes will be gained via the focus group discussion (FGD). CATA data analysis was processed using XLSTAT software with CATA Analysis tools while IPM data was processed with SensTools.Net applications with tools for IPA analysis. The cheese tea products most favored by customers based on the outcome of the CATA are products with a sweet scent, a milky aroma, cheesy aroma, a milky taste and a sweet taste, as well as the dominant emotional 'calm'. Product cheese tea C is the nearest product to its ideal product characteristics. In order to further improve the product “cheese tea C”, it is necessary to boost the strength of the characteristics of the creamy mouthfeel, the viscosity of the mouthfeel and the aroma of the cheese while at the same time reducing the intensity of the toasted aroma, the milky aroma, the umami, the salty taste, the milky taste and the sweet taste.